Acute Decompression for Peroneal Nerve Palsy Following Primary Total Knee Arthroplasty: A Report of Two Cases. Issue 1 (January 2015) - Erickson, Brandon J.; Brown, Nicholas; Fernandez, John; Della Valle, Craig J.
Abstract : Case: Two cases of peroneal nerve palsy following primary total knee arthroplasty are presented. Treatment included acute decompression of the peroneal nerve, with full neurological recovery. Conclusion: Acute peroneal nerve decompression is a viable option for patients with peroneal nerve palsy after primary total knee arthroplasty.